Assessment of knowledge and attitude about bio banking amongst the general public and their willingness to donate bio specimens from a hospital in India - K, Arathi; Vaswani, Vina; Hegde, Vijaya; Karikal, Arvind (Bangladesh Journal of Medical Science, 2024)
This study aims to know the attitude and perceptions of biobanks among the general public and their willingness to donate bio specimens from a hospital in India. Biobanks collect, store bio specimens for diagnosis, treatment and research purpose. According to modern bio banking, bio specimens needs to have standard operating procedures to do so. The bio specimen should be kept confidential and anonymous. Do they have an awareness of the role of biobanks? Do they know the concept of consent and implications of retaining specimens in biobanks? This paper evaluates these areas. A cross sectional study was conducted among general public above 18 years of age using convenience sampling. The data was obtained through a questionnaire which was distributed via online using Google forms and assessed the ethical perception of the general public regarding their willingness to donate own biological samples for teaching and research purposes and their awareness and attitude on biobanks. A total of 200 participants were included in the study. 71.4% participants did not have any prior knowledge about biobanks. 59.6% of the participants were willing to donate the biospecimens for advancement in medical research, benefit the society and future generation. 43.8% of respondents emphasised the main discouraging factor in participation in biobank research is that they have fear of sample exploitation. 37.9 percent participants responded that they would like to specify the scope for use when granting permission to use their sample for research. Biobank will advance in medical research only when medical institutes and government bodies’ install privacy, consent laws and initiate lot of awareness programmes to improve public perspectives and knowledge about biobanking. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S53-S59